Vietnam Association of Gastroenterology (VNAGE) consensus on the management of Helicobacter pylori infection - Quach, Duc Trong; Mai, Bang Hong; Tran, Mien Kieu; Dao, Long Van; Tran, Huy Van; Vu, Khanh Truong; Vu, Khien Van; Pham, Ho Thi-Thu; Bui, Hoang Huu; Ho, Dung Dang-Quy; Trinh, Dung Tuan; Nguyen, Vinh Thuy; et al. (Frontiers in Medicine, 2023)
Helicobacter pylori (H. pylori) infection is prevalent and has a rapidly increasing antibiotic resistance rate in Vietnam. Reinfection is quite common, and gastric carcinoma remains one of the most common malignancies, which is not uncommon to develop after successful eradication. The purpose of this consensus is to provide updated recommendations on the management of H. pylori infection in the country. The consensus panel consisted of 32 experts from 14 major universities and institutions in Vietnam who were invited to review the evidence and develop the statements using the Delphi method. The process followed the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. The consensus level was defined as ≥80% for agreement on the proposed statements. Due to the limited availability of high-quality local evidence, this consensus was also based on high-quality evidence from international studies, especially those conducted in other populations in the Asia–Pacific region. The panel finally reached a consensus on 27 statements after two voting rounds, which consisted of four sections (1) indications for testing and selection of diagnostic tests (2), treatment regimens, (3) post-treatment confirmation of H. pylori status, and (4) reinfection prevention methods and follow-up after eradication. Important issues that require further evidence include studies on third-line regimens, strategies to prevent H. pylori reinfection, and post-eradication follow-up for precancerous gastric lesions. We hope this consensus will help guide the current clinical practice in Vietnam and promote multicenter studies in the country and international collaborations.